Clinical Outcome in Children With Cancer With Two or More Microorganisms Isolated From Blood Cultures During Episodes of Fever and Neutropenia. Issue 1 (11th October 2022) - Ibáñez, Carolina; Torres, Juan Pablo; De La Maza, Verónica; Rivera, Salome; Valenzuela, Romina; Simian, Maria Elvira; Payá, Ernesto; Álvarez, Ana María; Contardo, Verónica; Martínez, Daniela; Claverie, Ximena; Santolaya, María Elena
Abstract : Background: Bacterial bloodstream infections are a major cause of morbidity and mortality in children with cancer and episodes of fever and neutropenia (FN). The aim of this study was to evaluate the clinical outcome in children with cancer with 2 or more microorganisms isolated from blood cultures during their episodes of FN. Methods: Between 2016 and 2021, children presenting with high-risk FN, admitted to any of the 6 participating hospitals in Santiago, Chile, were included in this study if they have positive blood cultures. We compared the clinical outcome of children with 2 or more microorganisms versus those with single agent isolation. Results: A total of 1074 episodes of high-risk FN were enrolled in the study period, of which 27% (298) had positive blood cultures and 3% (32) had 2 or more microorganisms isolated from blood cultures. The most frequent identified agents were Viridans group streptococci and Escherichia coli in 20%, followed by Coagulase negative staphylococci in 14%. Children with 2 or more microorganisms presented more days of fever (7 vs. 4 days, P = 0.02), needed longer courses of antimicrobial therapy (16 vs. 14 days, P = 0.04) and had higher mortality at day 30 (13% vs. 1%, P = 0.003). Conclusions: Children with cancer and FN with 2 or more microorganisms isolated from blood cultures had a worse clinical outcome than children with single agent isolation.